Cytogenetic Response Assessment to Imatinib Mesylate Therapy for Chronic Myeloid Leukemia in Iraqi Patients - M Haleem, Azhar (Diyala Journal of Medicine, 2020)
Background:Chronic Myeloid Leukemia (CML) is a disorder in myeloproliferative pluripotent hematopoietic primogenitor cells distinguished by huge reproduction of myeloid cells. CML cytogenetic distinguished by reciprocal translocation between the long arms of chromosomes 9 and 22 – to produce hallmark Philadelphia chromosome. Objective: The main goal of the current study was to identify the secondary chromosomal aberrations associated with the CML in Iraqi patients have positive Ph- chromosome using Imatinib theraby, at different phases of the disease. Patients and Methods: Practical part of this study was conducted from April/2018 to October/ 2019 in the Al-Kadumyha Teaching Hospital and Tissue Culture and Immunochemistry Lab/ University of Technology, for ≤ 18 years age for 75 CML eligible patients. Karyotypes of Philadelphia chromosome-positive bone marrow samples were examined for CML patients which were used Imatinib every twelve weeks. Secondary chromosomal abnormalities associated with development of disease were detected and calculated. Results: The average age of patients was 42± 8.7 years, while male to female ratio was (1.7:1), males number were 48 with percentage about 64%, while females number were 27 with percentage 36%, only 89.3% of CML patients showed a typical shape of Ph- chromosome, t(9: 22)(q34:q11.2), while 27 of 75 showed real cytogenetic response to Imatinib therapy. Conclusion: CML patients with high secondary chromosomal aberrations revealed low cytogenetic and molecular response to imatinib therapy, especially in blast phase.